Uma relação a dois: a história e a geografia nos primeiros anos do Instituto Histórico e Geográfico Brasileiro - Carlos, Lilian Beatriz (Universidade do Vale do Rio do Sinos, 2008)
History and Geography are domains that, despite being institutionalized at different moments in time, on the 19th century, developed and kept a close relationship. They were initially considered indissociated by Instituto Histórico e Geográfico Brasileiro (IHGB) membership. Founded by the Empire court on 1838, the institution initial objective was to gather documents which would lead to a future history and geography national writing. IHGB then led an operation which built territory and nationality. The politics unity legitimation and consolidation of brazilian territory were then thought by part of the imperial politics elite within the Institute. This is why this institution, despite being based on Institut Historique de Paris, was historically and also geographically built. This work presents an analysis on the relationship between geography and history as conceived by its membership, specially on the very first years, when in charge were those responsible by an Institute of double conception. The mains qu
Keywords: história do Brasil; historiografia; Instituto Histórico e Geográfico Brasileiro; Brazilian history; historiography; Ciências Humanas